Beliefs Regarding Classroom Management Style: Differences Between Urban and Rural Secondary Level Teachers - Nancy K. Martin; Zenong Yin (Journal of Research in Rural Education, 1999)
The primary objective ofthis study was to investigate differences between the classroom management style ofurban and rural secondary level educators. Data were collected utilizing the Attitudes and Beliefs on Classroom Control (ABCC) Inventory and demographics. The subject pool comprised 145 certified high school teachers employed by three public school districts in the southwest. The majority ofthe subjects were female (59%) and from urban school districts (73%). Rural teachers scored significantly more interventionist on the Instructional Management scale of the ABCC. Urban teachers scored significantly more interventionist on the People Management scale.